46 Feasibility and economic implications of ambulatory af ablation: a single-centre experience. (May 2019) - Reddy, Sathineni Ashwin; Nethercott, Sarah; Farag, Mohammed; Chattopadhyay, Rahul; Virdee, Munmohan
Abstract : Introduction: The widely accepted model for AF ablation involves overnight hospital stay post-procedure. Given the rising incidence of AF and number of AF ablations performed, streamlining of practice to minimise overnight stay could result in a significant reduction in waiting list times and procedure-related healthcare expenditure. Day case AF ablation has been carried out at Royal Papworth Hospital (RPH) since early 2017. We evaluated the feasibility, safety and efficacy of day case AF ablation at RPH. Method: Retrospective, single-centre study of 452 consecutive AF ablations in 448 patients at RPH between March 2017 and April 2018. Ablation method was selected at the operator's discretion. Vitamin K antagonists were continued and direct oral anticoagulants withheld for one dose pre-procedure in line with departmental policy. Ultrasound was not routinely used for femoral venous puncture. Haemostasis post-sheath removal was achieved with manual pressure. The consultant listing the patient at initial assessment subjectively determined suitability for day case. Complications were defined as any adverse procedure-related event. Success was defined as freedom from symptoms or demonstrable arrhythmia after 6 months following an initial 3-month blanking period. Results: Over the study period 129 out of 452 (28.5%) were planned day cases. Of these 128 (99.2%) were discharged on the same day; one patient was admitted due to late finish. 40 were performed as day cases despite being originally listed as inpatient procedures. Demographic and procedural data are summarised in table 1. There was no significant difference in age or sex between the groups. Of note, day case procedures were significantly shorter, more likely to commence in the morning and less likely to require general anaesthetic than overnight stays. Patients listed as day cases also had less far to travel. Procedural outcomes are summarised in table 2. Overall complication rate was 3.3%, with no significant difference between groups. One planned day case was complicated by intraprocedural phrenic nerve palsy from which a full recovery was made and another by transient migraine. A further case resulted in atrio-oesophageal fistula and death 3 weeks post-discharge. One patient discharged the same day despite planned overnight stay presented to his local DGH 3 days later with pulmonary oedema. Follow up data was available for 448 cases (99.1%). Procedural success rates were comparable between groups. At a cost of circa £400 for an overnight stay in RPH the overall cost saving attributable to providing AF ablation as a day case was £67, 200 over the 13 month period. Conclusion: Day case AF ablation is safe and efficacious even without strict standardisation of patient selection or procedural protocols in a high volume centre. Substantial reduction in healthcare expenditure can be achieved with more widespread implementation of ambulatory AF ablation. Conflict of Interest: nil